The effect of menstrual cycle phases on anaerobic power performance - Smirniotou, A.; Katsikas, C.; Salakos, N.; Kreatsas, G. (International Journal of Fitness, 2003)
The purpose of the present study was to evaluate the effect of menstrual cycle phases on anaerobic power performance in female collegiate track athletes. A total of 15 eumenorrheic women, who engaged in track activities at least 4 times a week for more than 60 min/day, were selected to complete the study. No one was using oral contraceptives. In order to evaluate the anaerobic power performance, the subjects underwent the following tests: squat jump, countermovement jump, repeated jumps-15 seconds and the Wingate test after 30 minutes of rest. The tests were performed during menstruation (M: between days 1-2), late follicular phase (LF: between days 10-13), and late luteal phase (LL: between days 23-26). Follicular and luteal phases were determined by analyses of daily basal body temperature chart (BBT) and confirmed by serum estradiol and progesterone assays during the preparatory test month and also during the testing month. The differences in the performances between M, LF, and LL phases were analyzed by analysis of variance (ANOVA) with repeated measures (cycle phases). The statistical significance was set at p<0.05. The data analyses from the present study indicate that there are no significant differences (p>0.05) in anaerobic power performance measured either with jumping tests or Wingate test among M, LF, LL, phases for these women. The results suggest that the menstrual phases in collegiate track athletes do not have an effect on the anaerobic power performance as measured in this study.